Measuring and categorizing the water-related downstream risks associated with mineral extraction in Honduras: How severe, and how distributed?. (October 2019) - Cuba, Nicholas; Fash, Benjamin; Rogan, John; Khan, Anam; Palma Herrera, José-Luis; Corrales Andino, Rafael Enrique; Mondragón Rivera, Claudia Nataly; Martinez, Sara; Sellwood, Scott
Abstract: Predictions about the spatial distribution of environmental impacts related to extractive industries have commonly assumed an inverse relationship between the severity of impact and distance from the site of extraction. However, because of the salience of water to both extractive industries and other livelihood strategies, many severe externalities of extractive development are experienced in areas hydrologically linked to the site of extraction, though these areas may not be those closest to mines themselves. This paper uses cadastral and remotely sensed data to model the spatial distribution of water, and extractive industries in Honduras and identify hydrological links between mines and downstream areas. Based on water availability, and the amount of upstream extractive development, it describes vulnerability to water-related risks from extractive industries in terms of severity as well as its concentration, measuring how local or spatially distributed are potential sources of impact. A consideration of risks experienced by agricultural producers indicates that small-scale farmers and large, commercial growers face distinctly different types of risk, and suggests that each group may pursue different strategies for mitigation. These strategies differ with respect to the spatial and administrative scales at which they would be pursued, as well as the degree to which they push for governance approaches focusing on spatially-defined, cadastral units of regulation or on broader regional and landscape impacts. Highlights: Governance of land and resource access for extractive industries is based on proximity. Environmental impacts of mining can be spatially extensive, especially those related to water use. Substantial agricultural land use is located downstream from mining in Honduras. Affected growers differ in how local, versus how distributed, are sources of toxicants. These differences suggest potential barriers to collaborative advocacy.